TRANSPORT FLEET SIZING BY USING MAKE AND BUY DECISION-MAKING - Stojanović, Djurdjica; Nikoličić, Svetlana; Miličić, Milica (Economic Annals, 2011)
Cost reduction is among the main quoted reasons for logistics outsourcing, while transport capacities and operations are among the most outsourced logistics areas. However, according to transaction costs theory, there is often room for transport insourcing. Furthermore, nowadays many authors stress that mixed solutions can give better results than “make” or “buy” alternatives.“Make or buy” decision-making normative models, methods, and procedures in transport planning are not much explored. Instead, research is rather focused on carrier selection techniques, whereby it is supposed that outsourcing transport capacities is the most suitable solution. The purpose of this paper is to contribute to the body of literature on classical “make-or-buy” decision-making in transport fleet sizing in a non-logistics enterprise. It goes beyond the basic “make or buy” decisionmaking, and intermediate solutions (i.e., “make and buy”) are explored. Practical directions are given according to theoretical principles, and a case study is used to exemplify the main deductions.The research also has practical implications. Many enterprises in transition economies have faced the question of what to do with their in-house transport fleets. The obtained results are of interest to merchants and manufacturing enterprises that already have a private transport fleet and are considering how to rationalize it.